Layanan Konseling Pribadi Introvert Agar Bisa Beradaptasi di Lingkungan Baru Menggunakan Konsep Komunikasi Interpersonal (Jurnal Bimbingan dan Konseling Islam, 2019)
This research discusses the introvert adar personal guidance services that can adapt in new environments using the concept of interpersonal communication. This study aims to determine introverted personal counseling services to be able to adapt to new environments using the concept of interpersonal communication. This type of research uses literature. Who wants to get a theory about the analysis of how introverted personal counseling services can adapt to new environments using the concept of interpersonal communication consisting of the opening stage, the explanation stage (exploration, behavior change (including some concepts of interpersonal communication) between others: a) Finding yourself b) Finding the outside world Building and maintaining harmonious relationships, assessment ,follow-up stages